Epistemic violence: A case for the decolonisation of South African business school curricula - Schutte, F. (South African Journal of Higher Education, 2019)
Since the #FeesMustFall movement and student protests of 2015 the decolonisation debate has become part of the ongoing narrative regarding higher education in South Africa. The purpose of this article is to investigate the concept of decolonisation and to identify different possibilities for the rethinking of decolonising academic knowledge production in the environment of higher education, of which business schools are a part. A systematic review of relevant and existing literature has been concluded. The findings of this review have shown that decolonisation is non-negotiable. Inclusive research from an African perspective can act as a starting point for this comprehensive project that is slowly starting to gain momentum. The project may benefit Africa and the West by providing a better understanding of each other when entering the same global market space.